Promoter Methylation Analysis on Microdissected Paraffin-Embedded Tissues Using Bisulfite Treatment and PCR-SSCP. (January 2001) - Bian, Y.-S.; Yan, P.; Osterheld, M.-C.; Fontolliet, C.; Benhattar, J.
Methylation-sensitive single-strand conformation analysis (MS-SSCA) is a new method of screening for DNA methylation changes. The combination of bisulfite modification and PCR results in the conversion of unmethylated cytosines to thymines, whereas methylated cytosines remain unchanged. This sequence conversion can lead to methylation-dependent alterations of single-strand conformation, which can be detected by SSCA. An analysis of mixtures of methylated and unmethylated DNA at known ratios revealed that the relative intensities of the corresponding bands following MS-SSCA were maintained. MS-SSCA was applied for methylation analysis of human p16 promoter region using genomic DNA obtained from either frozen, fixed, or microdissected fixed tissue sections. MS-SSCA is a rapid, specific, and semiquantitative approach that allows the detection of methylation of the p16 gene promoter. In reconstruction experiments, the method permits the detection of 10% or less of cells harboring a methylated p16 promoter. We have been successful in analyzing by MS-SSCA almost all (96%) tumor samples microdissected from archival paraffin-embedded fixed tissue sections and obtaining reproducible results. In addition, when microdissection was performed, the clonality of this genetic alteration could be identified.